2006
DOI: 10.1345/aph.1h396
|View full text |Cite
|
Sign up to set email alerts
|

Empiric Treatment of Uncomplicated Urinary Tract Infection with Fluoroquinolones in Older Women in Israel: Another Lost Treatment Option?

Abstract: Physicians who opt to treat UTI in postmenopausal women empirically should consider prescribing drugs other than fluoroquinolones. Concomitant longitudinal surveillance of both antibiotic utilization patterns and uropathogen resistance rates should become routine practice in this managed-care organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…In the North American Urinary Tract Infection Collaboration Alliance surveillance study, 5.5% and 5.1% of urinary E. coli isolates from outpatients in the United States and Canada were resistant to ciprofloxacin and levofloxacin, respectively (24). Similar results were reported for a cohort in Israel (12). Pseudomonas aeruginosa fluoroquinolone resistance is also problematic, with rates now exceeding 35% (7).…”
supporting
confidence: 54%
“…In the North American Urinary Tract Infection Collaboration Alliance surveillance study, 5.5% and 5.1% of urinary E. coli isolates from outpatients in the United States and Canada were resistant to ciprofloxacin and levofloxacin, respectively (24). Similar results were reported for a cohort in Israel (12). Pseudomonas aeruginosa fluoroquinolone resistance is also problematic, with rates now exceeding 35% (7).…”
supporting
confidence: 54%
“…The etiology of urinary tract infections (UTI) and the antibiotic resistance of uropathogens have been changing over the past years, both in the community and nosocomial infection. [11] However, there is not much information on etiology and resistance pattern of community acquired urinary tract infections (UTIs) in India. This retrospective study was done to compare the frequency and drug resistance pattern in uropathogens isolated from patients with urinary tract infections (UTIs) in IPD/OPD, Base Hospital Srikot and VCSG Medical College, Srinagar Garhwal, India.…”
Section: Introductionmentioning
confidence: 99%
“…However in resource poor settings may be take longer and, as in most of cases, the urine culture and susceptibility testing costs more than antibiotic treatment itself. Furthermore, the contemporary studies demonstrate that etiology of CA-UTI and their antibiotic sensitivity have been shown geographical variation; in majority of community acquired urinary tract infection, treatment decision is empiric, based on available guidelines and published studies 5,6 . To be successful and complained from subjects , The empirical treatment provided must be guided by clinical evidences as well as the safety profile and cost -effectiveness of the drug , and adhere to " antimicrobial stewardship "(using antibiotic in a way that helps to limit the development of resistance) 7 .…”
Section: Community Acquired Urinary Tract Infection (Cauti)mentioning
confidence: 99%